Structural Conditionality in IMF-Supported Programs : Evaluation Update 2018. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2018)
This Evaluation Update revisits the findings and conclusions of the 2007 Independent Evaluation Office evaluation on Structural Conditionality in IMF-Supported Programs. The Update found some progress in streamlining structural conditionality: the average number of structural conditions in IMF-supported programs declined one-third during 2010-17 as compared to 2003-07; structural conditions were more focused in areas of IMF core expertise; and compliance rates rose modestly. But challenges in applying structural conditionality remain salient. While borrowers appreciated the elimination of structural performance criteria in 2009 in the context of the switch from an ex post to a review-based structural conditionality framework, the Update found limited evidence that this change served to increase program ownership or reduce stigma. The Update found an overlap in responsibilities and burdensome requirements in programs with members of currency unions, notably where there were parallel EU programs. While World Bank-Fund cooperation on structural conditionality functioned reasonably well at the country level, staff and Executive Directors saw a need to strengthen institutional modalities to make collaboration less personality driven, more substantive, and systematically effective. Progress in improving Board documentation has been mixed. As in 2007, the Update found that program documents could do a better job at explaining the link between structural conditionality and program objectives. The IMF database on monitoring of Fund arrangements has significant shortcomings. The Fund no longer monitors the application of structural conditionality and it lacks a framework for assessing the effectiveness of structural conditionality in program design and outcomes across programs outside of periodic reviews that are spaced 5 or 6 years apart. The IMF's 2018 Review of Conditionality provides an opportunity to examine these issues. Special attention could be given to compliance and ownership, the depth of structural measures, and the broader impact of structural conditionality on policies and performance.